1965
DOI: 10.1149/1.2423405
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Studies on Zirconium and Hafnium in Molten LiCl-KCl Eutectic

Abstract: Electrode potential and polarographic studies have been made on solutions of zirconium and hafnium ions in molten normalLiCl‐normalKCl eutectic at 450°–550°C. Anodic dissolution of Zr at 450°C yielded Zr(IV), but at 550°C, chiefly Zr(II). Only Hf (IV) was observed over this range. Apparent standard electrode potentials were (mole fraction scale, Pt(II)/Pt(0) reference) normalZr)(II/normalZr)(0;−1.77normalv at 550°C normalZr)(IV/normalZr)(0;−1.86normalv at 450°C normalHf)(IV/normalHf)(0;−1.88normalv at 450°C;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
1

Year Published

1968
1968
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 0 publications
4
38
0
1
Order By: Relevance
“…The results of coulometric studies are similar to those reported by Baboian et af. ; (75) namely, up to 400°C zirconium was oxidized to Zr 4 +, whereas at 510°C and higher temperatures only Zr2+ was formed. Eon et af.…”
Section: Presently Important Solvent Systemsmentioning
confidence: 98%
See 1 more Smart Citation
“…The results of coulometric studies are similar to those reported by Baboian et af. ; (75) namely, up to 400°C zirconium was oxidized to Zr 4 +, whereas at 510°C and higher temperatures only Zr2+ was formed. Eon et af.…”
Section: Presently Important Solvent Systemsmentioning
confidence: 98%
“…(75) potentiometrically and voltammetrically. They showed that ZrH was the stable species produced in the melt by anodic dissolution of zirconium at lower temperatures.…”
Section: Presently Important Solvent Systemsmentioning
confidence: 99%
“…39 Electrolytic dissolution of Zircaloy in anhydrous molten 52 salts4° is also probably feasible; such a process has been proposed by ANL for LWR decladding (see Electrotransport). Aqueous electrolytic processes in nitric acid media disintegrate Zircaloy cladding and also dissolve the U0 2 .…”
Section: A110 Electrolytic Dissolutionmentioning
confidence: 99%
“…Although the method of measuring transition times used throughout this work (26) gave the ratios cited, other measurement techniques gave values closer to 3 for the mercury system. Two similar cases in which mixtures of oxidation states have been produced by electrochemical anodization of metals in fused salts are niobium in fused LiCI-KC1 (27), in which the ratio between Nb(1V) and Nb(II1) concentrations was approximately equal to 3, and zirconium in the same solvent, in which the proportion of Zr(I1) and Zr(1V) obtained is temperature dependent (28).…”
Section: Chronopotentiometric Measurementsmentioning
confidence: 99%